2006
DOI: 10.1542/peds.2006-0880
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Neurobehavior at Term Reflect Differing Perinatal Exposures in Very Preterm Infants

Abstract: Preterm infants at term equivalent showed alterations in motor behavior and higher cortically integrated functions. The pattern of abnormality in neurobehavior differed in relation to perinatal exposures. Neurobehavioral examination at term equivalent age is useful in evaluating the impact of neonatal intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 41 publications
2
66
2
7
Order By: Relevance
“…They required more handling, were more excitable and had more nonoptimal and asymmetric reflexes. 17 Although our findings agree that preterm infants required more handling and scored less in hypotonicity, comparison to term norms in other domains (quality of movement, excitability, lethargy, asymmetry, stress abstinence and hypertonicity) revealed different relationships. One of the major differences between our study and the previous report is that we used the published norms while they had their own controls for comparison.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…They required more handling, were more excitable and had more nonoptimal and asymmetric reflexes. 17 Although our findings agree that preterm infants required more handling and scored less in hypotonicity, comparison to term norms in other domains (quality of movement, excitability, lethargy, asymmetry, stress abstinence and hypertonicity) revealed different relationships. One of the major differences between our study and the previous report is that we used the published norms while they had their own controls for comparison.…”
Section: Discussioncontrasting
confidence: 61%
“…Factors that positively affected their scores included female sex, maternal antenatal steroids and receiving any amount of breast milk on discharge. 17 In the same population, the NNNS abnormalities were weakly associated with magnetic resonance imaging abnormalities. Of the summary scores, only nonoptimal reflexes showed association with individual magnetic resonance imaging changes, namely white matter signal abnormalities and gray matter gyral maturation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3 Ademais, a presença de comorbidades comuns na prematuridade (como hipóxia e displasia broncopulmonar) e o uso de alguns métodos assistenciais por períodos prolongados, tais como oxigenoterapia e ventilação mecânica invasiva, podem favorecer lesões neurológicas, provocando alterações transitórias ou duradouras, as quais podem variar desde um discreto atraso na aquisição das etapas motoras até o desenvolvimento de paralisia cerebral. 1,[4][5][6] Para muitos recém-nascidos prematuros, a permanência em Unidade de Terapia Intensiva (UTI) é essencial à manutenção da vida. Porém, no ambiente da unidade neonatal, a exposição constante à estimulação excessiva (ruídos, luminosidade, procedimentos dolorosos, entre outros) em crianças neurofisiologicamente imaturas pode desencadear alterações motoras e hemodinâmicas.…”
Section: Introductionunclassified
“…14,25 In this study, using a scale validated for neu- neurobehavioral changes in extreme preterm infants using the NNNS and reported that female babies exhibited better performance than males for "quality of movement". 29 It is known that higher levels of stress hormones are found in male newborn infants when they are subjected to stressful procedures. 30 It is possible that intrauterine growth restriction causes different cortical growth and organization changes during intrauterine life for male and female fetuses, depending on the predominant hormonal influence, which would explain the neurobehavioral differences observed in male and female SGA newborn infants during their first days of life.…”
Section: 2mentioning
confidence: 99%